Two Kinds of Rationality : Kibbutz Democracy and Generational Conflict - Evens, T. M. S. (Book collections on Project MUSE., 1995)
Beginning with a discussion of mind-body dualism in social anthropology, Evens presents a profound theory of human conduct that deploys notions of hierarchy and practice. He uses the case study of an Israeli kibbutz to address the central anthropological problem of rationality. Of particular interest is Evens's interpretation of the Genesis myth, along with his reading of Rousseau's revision of this myth, as a paradigm of generational conflict and the kibbutz's logic of moral order.